ENT 530 Social Media Portfolio : Kriuk Kriuk / Muhammad Ammar Naim Murad - Murad, Muhammad Ammar Naim (2019)
Kriuk Kriuk (KK) offers food products for customers, providing the variety of flavours that gives high satisfaction to the customer.